Ezra: a new translation with introduction and commentary - Eskenazi, Tamara Cohn (The Anchor Yale Bible Commentaries, 2023)
A new translation and commentary on the biblical book of Ezra by the renowned author of two award-winning biblical commentaries The book of Ezra is a remarkable testament to a nation’s ability to survive and develop a distinctive identity under imperial rule. But Ezra is far more than a simple chronicle; it constitutes a new biblical model for political, religious, and social order in the Persian Empire. In this new volume, Tamara Cohn Eskenazi outlines how the book of Ezra documents the radical transformation that followed reconstruction after the fall of Jerusalem and Judah. The extensive introduction employs literary and historical methodologies to highlight the book’s innovations, including its textualization of the tradition, as well as the unprecedented role of the people as chief protagonists. The translation and commentary incorporate evidence from ancient and contemporaneous primary sources from Egypt, Babylonia, Greece, and Persia, along with new archaeological studies of Judah. With great care and detail, Eskenazi demonstrates how the book of Ezra creates a blueprint for survival after destruction, shaping a new kind of society and forging a new communal identity